THE INFLUENCE OF QUALITY AMBIDEXSTERITY ON COST LEADERSHIP, DIFFERENTIATION, FOCUS, DYNAMIC CAPABILITIES AND ITS IMPLICATIONS ON FINANCIAL PERFORMANCE (EMIPIRICAL STUDY ON OIL DRILLING COMPANIES IN INDONESIA) - Oscar Jayanagara; Hendra Hartanto (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
This research aims to investigate about the effect of the Quality Ambidexterity on Cost Leadership, Differentiation, Focus, Dynamic Capability, and their implication to Financial Performance. The methodology of this research was explanatory research with hypothesis testing for examining ten hypotheses. Populations were the Oil Drilling Companies in Indonesia, with sample size were 200 companies. Data for this study were collected using questionnaires and SEM (Structural Equation Modeling) was employed for data analysis techniques. The results of this research were as follows: (1) Quality Ambidexterity positively and significantly influenced Cost Leadership; (2) Quality Ambidexterity positively and significantly influenced Differentiation; (3) Quality Ambidexterity positively and significantly influenced Focus; (4) Quality Ambidexterity positively and significantly influenced Dynamic capability; (5) Cost Leadership positively and significantly influenced Financial Performance; (6) Differentiation positively and significantly influenced Financial Performance; (7) Focus, positively and significantly influenced Financial Performance; (8) Dynamic Capability, positively and significantly influenced Financial Performance; (9) Quality Ambidexterity positively and significantly influenced Financial Performance; (10) Ambidexterity, Cost Leadership, Focus, Dynamic Capability positively and significantly influenced Financial Performance, and the most significant is the influence of Quality Ambidexterity to Cost Leadership. All of ten hypotheses which proposed in this research were being given can be accepted. Quality Ambidexterity as an independent variable was the strongest influence on Cost Leadership, and Cost Leadership was the strongest influence on Financial Performance. This dissertation also provides discussion on the findings as well as limitations, theoretical and practical contribution, theoretical and managerial implications of the study, and suggestions for future research.